An interesting case report on obstructed labour with prune belly syndrome - Somasundaran, Aiswaria; Sandra K. Unni; Naseema Beevi Ahmed Khan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Prune belly syndrome is a rare disorder of uncertain etiology characterized by a triad of deficient abdominal musculature, cryptorchidism and urinary tract abnormalities. This condition varies in its severity which makes diagnosis challenging during early antenatal ultrasound scan. 34-year-old G4P3L3 who was counselled for pregnancy termination at 20 weeks in view of multiple anomalies detected on antenatal ultrasound. At 34 weeks of gestation presented to our institution in active phase of labour and progressed to obstructed labour and was managed by ultrasound guided fetal abdominal tapping. We conclude that suspicion of such anomalies through an early antenatal scan require further follow-up with an experienced ultrasonographer and maternal–fetal medicine specialist for a decision to be made antenatally regarding the course of pregnancy and delivery management based on the severity of the condition in a tertiary center.